PENINGKATAN EKONOMI MASYARAKAT DESA WUKIRSARI MELALUI PROGRAM SMART FARMING PENGOLAHAN LAHAN DAN HASIL PADI BERBASIS IOT - Khalil Sidik; Gatot Santoso; Amir Hamzah; Suwanto Raharjo; Emy Setyaningsih (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Tri Sedyo Manunggal Farmers Group, Pandan Hamlet, Wukirsari Village, Cangkringan Sleman District, Yogyakarta faces challenges in monitoring the quality of rice crops, using pesticides to eradicate pests, and depending on electricity from PLN and fuel to operate UV lamps. Therefore, to overcome this problem, the activity implementation team developed a smart farming tool that can monitor pH, leaf color and pest volume. Pest traps use ultraviolet (UV) lights with relays as automatic switches. The entire system is powered by solar energy, creating an environmentally friendly solution with no electricity costs from PLN. Integration with IoT enables remote control and monitoring. Implementation of activities was carried out through socialization of smart farming tools, as well as training in use, installation and maintenance of the tools. From the results of the implementation of activities, it can be seen that this tool operates effectively with a high level of accuracy, and provides important information, such as the need for urea fertilizer, the amount of lime for acidic soil, and sulfur to treat alkaline soil, in order to achieve the ideal pH. In addition, this tool is effective in catching pests without pesticides, including planthoppers, grasshoppers and grasshoppers. So, farmers make the right and efficient decisions, increase crop yields and manage time. This initiative is an important step towards sustainable and technology-based agriculture.